2015
DOI: 10.3168/jds.2014-8993
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled β-lactoglobulin–oleic acid and β-lactoglobulin–linoleic acid complexes with antitumor activities

Abstract: β-Lactoglobulin (β-LG) can bind to fatty acids such as oleic acid (OA) and linoleic acid (LA). Another whey protein, α-lactalbumin (α-LA), can also bind to OA to give the complex α-LA-OA, which has antitumor properties. Based on reports that the activity of α-LA-OA is highly dependent on OA, as well as the acquisition of similar complexes using other proteins, such as lysozyme and lactoferrin, we speculated whether β-LG could also kill tumor cells after binding to other fatty acids. Therefore, we prepared comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…Alpha-lactalbumin protein triggers cell death in normal rat intestinal epithelial cells (63) and virus-transformed mouse leukaemia cells (64). These results and HAMLET results showing HAMLET cytotoxicity superior to that of the oleic acid alone (3)(4)(5)15,17,38,44,50,54), indicate that α-lactalbumin protein is also playing role in HAMLET-induced cell death.…”
Section: Oleic Acid Is the Main Active Componentmentioning
confidence: 63%
See 4 more Smart Citations
“…Alpha-lactalbumin protein triggers cell death in normal rat intestinal epithelial cells (63) and virus-transformed mouse leukaemia cells (64). These results and HAMLET results showing HAMLET cytotoxicity superior to that of the oleic acid alone (3)(4)(5)15,17,38,44,50,54), indicate that α-lactalbumin protein is also playing role in HAMLET-induced cell death.…”
Section: Oleic Acid Is the Main Active Componentmentioning
confidence: 63%
“…Other studies found that the protein-lipid complex is more cytotoxic than similar amounts of oleic acid or sodium oleate alone (3)(4)(5)15,17,38,44,50,54). It is not yet clear whether these are true differences in cytotoxicity for the different protein carriers of oleate, or whether these different results reflect difficulties in solubilising oleic acid alone for delivery in water-based cellular systems, or are a result of accuracy and precision in measuring the oleate amounts present in the HAMLET-like compounds.…”
Section: Oleic Acid Is the Main Active Componentmentioning
confidence: 96%
See 3 more Smart Citations